P PEMANFAATAN FRAMEWORK LARAVEL UNTUK SISTEM INFORMASI PADA TOKO BATIK RATO EBHU BERBASIS WEB - Amalia, Baiq Rizky; Saurina, Nia (Melek IT : Information Technology Journal, 2022)
Along with the development and progress of information technology is very rapid in human life. Rato ebhu batik shop is a batik shop that sells and markets its products conventionally. Therefore, a web-based Rato Ebhu shop information system was made using the Laravel framework to make it easier for writers to build an information system on a web-based Rato Ebhu batik shop, by utilizing the built-in features of Laravel, namely artisan, making it easier for authors to create tables in the database as well as MVC features so that authors can easily write program code. This system is made in order to reach more customers and to simplify the sales process and as a marketing tool. The design used to build this system includes data collection, literature study and interviews with researchers which are then carried out by designing, coding and testing the system. The laravel framework can be implemented well and easily so that the system can be built easily and quickly so that the information system at the web-based ratho ebhu batik shop can be built.